Penetapan kadar fenolik total ekstrak etanol, fraksi etil asetat dan n-heksan daun kopi robusta (Coffea canephora Pierre ex A. Froehner) dengan metode spektrofotometri Uv-Vis - Yulia Nanda Putri; Muhammad Amin Nasution; Ridwanto Ridwanto; Anny Sartika Daulay (Journal of Pharmaceutical and Sciences, 2023)
Phenolic compounds have various biological effects, such as antioxidant activity, can reduce the risk of cancer, coronary heart disease, stroke and other neurodegenerative diseases. Robusta coffee leaves (Coffea canephora Pierre ex A. Froehner) have activity as antioxidants because they contain abundant phenolic compounds. This study aims to determine the ratio of total phenolic levels between ethanol extract, ethyl acetate fraction and n-hexane fraction from robusta coffee leaves. In this study, the first step taken was a characterization test on simplicial powder and robusta coffee leaves macerated with 70% ethanol solvent. The maserat obtained is further fractionated with n-hexane and ethyl acetate. Followed by phytochemical screening on coffee leaf samples. Furthermore, the extract, n-hexane fraction and ethyl acetate determined total phenolic levels using visible spectrophotometry at a wavelength of 749 nm. Determination of total phenolic levels using the Folin-Ciocalteu method with gallic acid standards. Total phenolic levels are expressed in mg gallic acid equivalent (GAE) per gram of simplicial. The results showed that 70% ethanol extract of robusta coffee leaves had a total phenolic content of 25.9438± 0.0889 mg GAE/g. From the fractionation results show that the ethyl acetate fraction of robusta coffee leaves has a greater total phenolic content compared to the n-hexan fraction of 28.048 ± 0.3692 mg GAE / g and followed by the n-hexane fraction of 15.5231 ± 0.7213mg GAE / g. This is because the fractionation method can increase the desired compound content by removing or separating unwanted compounds, thus making the compound results in the use of fractions purer.